Congenital pulmonic and aortic stenosis in Newfoundland dogs: Results of a 14-year French cardiovascular screening program (921 dogs). - Valérie Chetboul; Constance Fauveau; Peggy Passavin (PLoS ONE)
Introduction Aortic stenosis (AS) and pulmonic stenosis (PS) are two of the most common canine congenital heart diseases (CHD), with a high relative risk for Newfoundland dogs to develop inherited subvalvular AS. For this reason, a cardiovascular screening program has been set up by the French Newfoundland kennel club in order to manage mattings and reduce AS prevalence. Materials and methods The records of untreated and non-anesthetized adult Newfoundland dogs screened between 2010 and 2023 were retrospectively reviewed. All dogs underwent physical examination and standard transthoracic echocardiography with concomitant ECG tracing. All examinations were reviewed by one single board-certified specialist in cardiology. Results A total of 921 dogs were screened during the study period (female:male sex ratio = 1.94, median age [IQR] = 1.9 years [1.6-2.7], body weight = 55.0 kg [50-60]). For most dogs (90.6% for AS and 91% PS), a single examination was required to obtain a definitive cardiac status, although most operators (122/133 = 91.7%) were non-specialist general practitioners. Out of the 921 screened dogs, 913/921 (99.1%) and 919/921 (99.8%) were respectively free of AS and PS, with no AS and PS detection during the last 3 years of the program. The inbreeding coefficient, which was assessed from the pedigree analysis of all screened dogs except one, was not significantly different between dogs with either AS (0.59%; P = 0.86) or PS (0.39%; P = 0.72) and those without any arterial stenosis (0.39%). Conclusion This 14-year cardiovascular screening program has experienced a strong involvement of veterinarians, breeders, and owners throughout France. Unlike reports from other European and North American countries, this program suggests the low and decreasing prevalence of both AS and PS in the Newfoundland breed in France.